2018
DOI: 10.1590/0102-311x00110716
|View full text |Cite
|
Sign up to set email alerts
|

User satisfaction with public and private dental services for different age groups in Brazil

Abstract: This article aimed to describe the levels of user satisfaction in different age groups and to study the association between user satisfaction and different types of dental services in a representative sample of Brazilians. This study is based on the Brazilian Oral Health Survey, which evaluated the dental health of adolescents, adults and older adults in 177 Brazilian cities. The outcome variable was user satisfaction, related to the last dental visit, evaluated in a five-level Likert-type scale. The main expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
8
1
4
Order By: Relevance
“…The satisfaction increased with aging. This finding is in agreement with data reported in a previous study conducted in Brazil, in which the youngest participants reported the least satisfaction with oral health services [20]. Similar findings were reported in studies conducted in the primary care setting in Saudi Arabia [21] as well as at hospital services in Sweden [22] and the United States [23].…”
Section: Discussionsupporting
confidence: 92%
“…The satisfaction increased with aging. This finding is in agreement with data reported in a previous study conducted in Brazil, in which the youngest participants reported the least satisfaction with oral health services [20]. Similar findings were reported in studies conducted in the primary care setting in Saudi Arabia [21] as well as at hospital services in Sweden [22] and the United States [23].…”
Section: Discussionsupporting
confidence: 92%
“…A elevada satisfação com o serviço, observada nesta pesquisa, está de acordo com os resultados sobre a satisfação dos usuários com os serviços odontológicos no Brasil, tanto públicos quanto privados, em diferentes grupos etários 9 .…”
Section: Discussionunclassified
“…But possibly in states with better socioeconomic and health indicators, having only the dental care plan would not be a good indicator of better socioeconomic status. 32,33 Recalling that, as described in the methodology, this covariate concerns population proportion with some plan only for dental care, that is, we are not analysing medical plan.…”
Section: Discussionmentioning
confidence: 99%